Potential of Fecal Sludge Briquette as Biofuel: A Review - Khotimah, Siti Nurul (INSTEP Network, 2025)
Fecal sludge from fecal wastewater treatment may create problem to environment and human health as Its high production number and its hazardous content. The high volume of fecal sludge production not only reflects the scale of sanitation needs but also signifies a substantial opportunity for renewable energy generation by transforming the fecal sludge to briquettes. This article is a critical review to evaluate the potential of fecal sludge, especially about its characteristics as a raw material, the method to create the briquettes, the briquette composition and finally its performance regarding the fecal sludge composition. Interestingly, even though fecal sludge is hazardous as the high pathogen level such as bacteria, worm and its egg, they will die after drying and carbonizing process. Hence, it will be safe to utilize the fecal sludge briquettes for human need. Comparing the calorific value of fecal sludge briquettes and coal (fossil fuel which has high energy value), the fecal sludge’s energy is about 3 times lower. This mean, if it is expected to achieve the fecal sludge briquettes’ calory equivalent to the coal, the number of fecal sludge briquettes should be multiplied 3 times.